The role of professional development in developing the competencies of middle school teachers in Al-Aziziyah Municipality: A field study (Al-Farooq Journal of Sciences, 2026)
This study aims to investigate the role of professional development in developing the professional competencies of middle school teachers in Al-Aziziyah Municipality, Libya, and to examine the relationship between professional development and teachers’ professional competencies. The study is based on the contemporary view of teachers as active professionals who need continuous learning opportunities to develop instructional, assessment, technological, communication, and reflective competencies, A descriptive-correlational analytical design is proposed. Professional development is conceptualized through continuous training, collaborative professional learning, mentoring and feedback, reflective practice, and educational technology. Teachers’ professional competencies are examined through planning, instructional implementation, classroom management, assessment, technology integration, communication, and continuous professional learning.The theoretical framework draws on Desimone’s (2009) conceptual framework for studying the effects of professional development and on Darling-Hammond et al.’s (2017) review of 35 methodologically rigorous studies. The latter identified seven common characteristics of effective professional development: content focus, active learning, collaboration, modeling of effective practice, coaching and expert support, feedback and reflection, and sustained duration.The study is expected to contribute to the development of evidence-based professional development programs for middle school teachers in Al-Aziziyah Municipality and to support the alignment of professional learning opportunities with teachers’ actual needs and classroom practices.
Keywords: Professional Development, Teacher Competencies, Middle School Teachers, Professional Learning, Teacher Development, Al-Aziziyah Municipality